2008
DOI: 10.1016/j.bbamem.2008.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization of the lipid matrix in intact Stratum corneum using ATR-FTIR spectroscopy

Abstract: ATR-FTIR spectroscopy is useful in investigating the lateral organization of Stratum corneum (SC) lipids in full-thickness skin. Based on studies of the thermotropic phase transitions in n-tricosane and in excised human skin, the temperature dependence of the CH2 scissoring bandwidth emerged as a measure of the extent of orthorhombic and hexagonal phases. This dependence provides a simpler measure of the lateral order in lipid assemblies than the common spectroscopic approaches based on difference spectra, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
156
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 54 publications
13
156
0
Order By: Relevance
“…It is not clear how the cholesterol molecules are distributed between the phases. Several studies with isolated SC, model lipid mixtures and human skin equivalents have shown presence of phase-separated, pure cholesterol crystals [49,98]; little is known about them.The solid-solid phase transition (between OR and HEX) occurs at physiologically relevant temperatures, around 35-40°C [66,99]. The solid-liquid transition (between OR or HEX and LIQ) occurs at non-physiological temperatures, around 70°C, but it can be caused by changes in the phase composition, for example by topical application of chemicals [85].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear how the cholesterol molecules are distributed between the phases. Several studies with isolated SC, model lipid mixtures and human skin equivalents have shown presence of phase-separated, pure cholesterol crystals [49,98]; little is known about them.The solid-solid phase transition (between OR and HEX) occurs at physiologically relevant temperatures, around 35-40°C [66,99]. The solid-liquid transition (between OR or HEX and LIQ) occurs at non-physiological temperatures, around 70°C, but it can be caused by changes in the phase composition, for example by topical application of chemicals [85].…”
mentioning
confidence: 99%
“…The solid-solid phase transition (between OR and HEX) occurs at physiologically relevant temperatures, around 35-40°C [66,99]. The solid-liquid transition (between OR or HEX and LIQ) occurs at non-physiological temperatures, around 70°C, but it can be caused by changes in the phase composition, for example by topical application of chemicals [85].…”
mentioning
confidence: 99%
“…The information tells us about several micrometres of surface; thus, it is also a useful method for analysing skin [45,46]. ATR-FTIR spectra can give us information about hydration of skin [47], structure of proteins [48] and lipids [49] and about their changes during skin treatment by chemical or other drug enhancers [50,51]. There are several vibrational bands associated with chemical functional groups.…”
Section: Diagnostics Of Barrier Properties Of the Skin-tewl (Transepimentioning
confidence: 99%
“…Vibrational bands at 2850 and 2920 cm −1 belong to CH 2 symmetric and asymmetric stretching modes, respectively [52]. The absorbance of the spectrum decreases as the thickness of the skin decreases and the wavenumber indicates a change in chain conformation, especially a change in peak shape [49].…”
Section: Diagnostics Of Barrier Properties Of the Skin-tewl (Transepimentioning
confidence: 99%
“…It is poorly absorbed from the gastrointestinal tract; Gastrointestinal absorption of vitamin B12 depends on the presence of sufficient intrinsic factor . Percutaneous absorption of B 12 in guinea pig and rat has been investigated and it was demonstrated that absorption was more efficient from an ethanol solution than from water or dimethyl sulfoxide, and also it was independent of the quantity of vitamin applied to a given area [9].…”
Section: Introductionmentioning
confidence: 99%